Sequence-based characterization of Escherichia coli in fresh produce and environmental samples in selected urban farms in Metro Manila, Philippines - PIERANGELI G. VITAL; MA. CHRISTINE JASMINE F. SABIO; DONNABEL C. SENA (Asian Journal of Agriculture, 2025)
Abstract. Vital PG, Sabio MCJF, Sena DC. 2025. Sequence-based characterization of Escherichia coli in fresh produce and environmental samples in selected urban farms in Metro Manila, Philippines. Asian J Agric 9: 582-589. The prevalence of Escherichia coli is well-documented in the Philippines, and this commonly food- and water-borne pathogen poses a public health risk. Serotyping is being done to determine the pathogenicity or clinical relevance of an isolate. With whole genome sequence (WGS) data becoming more available and the development of user-friendly online platforms for processing such data becoming more popular, an accurate strain identification can be made. The current study used web-based methods for multilocus sequence typing (MLST) and serotyping based on O and H antigens to characterize 30 E. coli isolates from a total of 117 samples collected from selected urban farms in the Philippines. Thirty-two out of 117 samples were confirmed to harbor thermotolerant E. coli. Sequence type 155 (ST 155), which is documented to be associated with zoonotic infections and antibiotic resistance, was observed among the isolates along with 25 other sequence types of E. coli. Several non-O157 Shiga toxin-producing E. coli (STEC) serotypes were detected, including O115:H11, O75:H10, O9a:H4, O148:H8, and O18ac:H21. Rare serotypes and incomplete serotypes (H-types only) were also detected. Our study highlights the utility of whole genome sequence-based strain characterization. The results of this study can be used for understanding contamination dynamics in the food chain and aiding agricultural food safety and outbreak investigations.